2018
DOI: 10.1111/ctr.13334
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of hepatic fibrosis in responders to direct‐acting antivirals for recurrent hepatitis C after liver transplantation using noninvasive methods

Abstract: Successful eradication of recurrent hepatitis C virus (HCV) infection following liver transplantation (HCV) improves graft survival. This study aimed at evaluation of hepatic fibrosis changes among long-term responders to DAA therapy for recurrent HCV after liver transplantation using noninvasive methods. Patients with significant hepatic fibrosis (≥F2) who achieved SVR12 after treatment with DAAs for recurrent HCV were included (n = 52). Hepatic fibrosis status was assessed, noninvasively, by calculation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The decrease in these scores must have occurred due to a reduction in serum aminotransferase levels, and the fact that there was no significant increase in the number of platelets, during or after antiviral therapy. The low increase in the number of platelets in our study was possibly due to the absence of thrombocytopenia in our patients before starting the therapy with DAAs, as was also seen in the study by Omar et al 35 . Accordingly, in a study by Hsu et al 36 in non-transplanted patients with CHC treated with DAAs, an increase in the number of platelets was observed only in patients who presented with thrombocytopenia before the treatment 36 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The decrease in these scores must have occurred due to a reduction in serum aminotransferase levels, and the fact that there was no significant increase in the number of platelets, during or after antiviral therapy. The low increase in the number of platelets in our study was possibly due to the absence of thrombocytopenia in our patients before starting the therapy with DAAs, as was also seen in the study by Omar et al 35 . Accordingly, in a study by Hsu et al 36 in non-transplanted patients with CHC treated with DAAs, an increase in the number of platelets was observed only in patients who presented with thrombocytopenia before the treatment 36 .…”
Section: Discussionsupporting
confidence: 81%
“…These data indicate a reduction in the progression of CHC to cirrhosis and, consequently, in the number of cases requiring liver transplantation as a consequence of HCV infection. However, there are few studies evaluating fibrosis regression after treatment of CHC with DAAs in liver-transplanted patients 35 . Indeed, Omar et al found a progressive improvement in the degree of liver fibrosis, as indicated by elastography and serum scores, 12 and 18 months after the treatment of CHC with DAAs in 52 liver transplant patients 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Sustained virologic response (SVR) to anti-HCV therapies improves surrogate indicators of fibrosis such as liver stiffness in short-term, which is followed by gradual regression of histological fibrosis. 23,25 However, SVR rate with DAA post transplantation can be as low as 50% and adverse event rates can be as high as 75% when progressed to decompensated liver disease. 26 Therefore, prediction of fibrosis progression will remain relevant in a subset of post-transplant patients with HCV infection.…”
Section: Pls Is Associated With 5-year Fibrosis Progression After Liv...mentioning
confidence: 99%
“…However, fewer studies have evaluated noninvasive assessments of liver fibrosis in LT recipients. Liver fibrosis indices based on laboratory tests, such as APRI ( 15 ) and FIB‐4 index, ( 16‐18 ) have been reported to be useful to evaluate graft fibrosis. Yoshino et al reported that liver stiffness measurements by ARFI were more useful to predict graft fibrosis after LT than blood test–based indices that are profoundly affected by clinical factors other than the extent of liver fibrosis.…”
mentioning
confidence: 99%